Molecular Forensic Investigations into Animal Sexual Abuse - Natha, Khilona (Department of Pathology, 2021)
Animal sexual abuse (ASA) involves the sexual molestation of animals by humans. The identification of semen provides a legally-accepted indicator that sexual activity occurred, while forensic DNA analysis provides a lead to a potential suspect. After conducting a systematic literature review, no previous research investigating semen and/or DNA recovery from animals over time was found. Therefore, this pilot study aimed to assess the recovery of human semen and DNA from animal fur over a two-week period to establish baseline data pertaining to evidence retention in the ASA context. This pioneer study also attempted to contribute towards the development of a suitable animal fur model on which to perform experiments. Daily swabbing and testing of semen from three fur models (unpreserved baboon fur, preserved nyala hides and faux fur) showed that semen could still be detected at 14 days using standard presumptive and confirmatory tests. Although DNA degradation showed a statistically significant increase over time, forensically usable DNA profiles (≥ 12 fully typed short tandem repeat loci) were consistently obtained. There was significantly higher DNA degradation in samples from the baboon fur compared to the others, while DNA concentrations were significantly different between each fur model. These differences highlight that future research must consider the choice of fur model to best represent the animal of interest; e.g. dissected fur from a recently deceased animal would best mimic a fatal ASA case. The insight regarding the choice of animal model hopes to be of benefit for future research, which should focus on the influence of more realistic variables (e.g. movement and body heat) on semen and DNA retention on animal fur. Overall, this study successfully generated baseline data, and provides a foundation for additional research, which hopes to eventually assist in the interpretation of forensic evidence in the global burden of ASA.